SYMBOLISM AND ECOLOGY IN THE LUBARAN TRADITION: A DESCRIPTIVE STUDY OF THE LOCAL WISDOM OF LOGANDU KARANGGAYAM KEBUMEN: SYMBOLISM AND ECOLOGY IN THE LUBARAN TRADITION: A DESCRIPTIVE STUDY OF THE LOCAL WISDOM OF LOGANDU KARANGGAYAM KEBUMEN - Khotimah, Husnul; Birsyada, Muhammad Iqbal (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2025)
Indonesian farmers are closely connected to various ritual traditions, these traditions form local wisdom in ecological communities, The Logandu Karanggayam Kebumen Central Java community cannot be separated from the existence of ancestral traditional rituals which include various interconnected elements, The rapid progress of science and technological developments as well as the influence of modern globalization, are increasingly eroding local wisdom in society, Such conditions can reduce the sacred value and meaning of existing traditions, The Lubaran tradition is still carried out and preserved by farmers in Logandu village, Karanggayam, Kebumen, Central Java, The implementation of the Lubaran Tradition has two motive parameters, namely because of motive and in order to motive, The research aims to identify the meaning, implementation process and role of the community in preserving traditions, The object of this study focuses on the symbolic meaning and purpose of carrying out the Lubaran tradition in the farming community of Logandu village, Karanggayam, Kebumen, Central Java, This local wisdom is certainly full of meaning and cultural values, so it is very important to conduct studies as an effort to introduce one aspect of culture to the next generation of the nation, The research method used is qualitative with an ethnographic approach,